SIGNIFICANCE OF FINLAND EDUCATION IN INTERNATIONAL ASSESSMENT PROGRAMS (American Journal of Technology and Applied Sciences, 2023)
In this article, opinions are expressed that Finland is among the advanced foreign countries in terms of the experience of the educational system and the quality of education. We are witnessing that it occupies the highest indicators in international evaluation programs.